Ishchenko О. Intertextual Paradigm in the Novels by Myroslav Dochynets - О. Ishchenko (Philological Treatises, 2020)
The article is devoted to the study of artistic features of intertextuality in novels «Centenarian. Confession on the Pass of the Spirit», «Svitovan. Studies under the Celestial Dome», «Highlander. Waters of our Lord’s Riverbeds», «The Digger of Wells. The Diary of the Richest Man of the Mukachevo Dominion», «Maftei. The Book is Written with a Dry Pen» by the modern Ukrainian writer M. Dochynets. The main intertextual elements (paratextuality, actual intertextuality, metatextuality) and the forms of their realization (citations, allusions, reminiscences, paraphrases, etc.) in the works of the prose writer are investigated. It was found that M. Dochynets in his novels most often uses theological (Bible, religious texts), mythological (ancient Greek myths), literary (Ukrainian and Foreign), folklore sources (songs, spells, proverbs), appealing to the works of famous philosophers and thinkers of the past (Gregory Skovoroda, Socrates, Pythagoras). As an example of numerous artistic facts, the influence of intertextual elements and the forms of their implementation on the topic, storyline, imaginative level of the novels of the writer has been proved. The intertextuality in novels «Centenarian. Confession on the Pass of the Spirit», «Svitovan. Studies under the Celestial Dome», «Highlander. Waters of our Lord’s Riverbeds», «The Digger of Wells. The Diary of the Richest Man of the Mukachevo Dominion», «Maftei. The Book is Written with a Dry Pen» by M. Dochynets as a main feature of author’s idiostyle is analized.